Upfront treatment with mTOR inhibitor everolimus in pediatric low‐grade gliomas: A single‐center experience. Issue 10 (27th December 2020) - Cacchione, Antonella; Lodi, Mariachiara; Carai, Andrea; Miele, Evelina; Tartaglia, Marco; Megaro, Giacomina; Del Baldo, Giada; Alessi, Iside; Colafati, Giovanna Stefania; Carboni, Alessia; Boccuto, Luigi; Diomedi Camassei, Francesca; et al.
Abstract: Pediatric low‐grade gliomas (pLGGs) are the most frequent brain tumor in children. Adjuvant treatment, consisting in chemotherapy and radiotherapy, is often necessary if a complete surgical resection cannot be obtained. Traditional treatment approaches result in a significant long‐term morbidity, with a detrimental impact on quality of life. Dysregulation of the mitogen‐activated protein kinase (MAPK) pathway is the molecular hallmark of pLGGs and hyperactivation of the downstream mammalian target of rapamycin (mTOR) pathway is frequently observed. We report clinical and radiological results of front‐line treatment with everolimus in 10 consecutive patients diagnosed with m‐TOR positive pLGGs at the Bambino Gesù Children's Hospital in Rome, Italy. Median duration of treatment was 19 months (range from 13‐60). Brain magnetic resonance imaging showed stable disease in 7 patients, partial response in 1 and disease progression in 2. Therapy‐related adverse events were always reversible after dose reduction or temporary treatment interruption. To the best of our knowledge, this is the first report of everolimus treatment for chemo‐ and radiotherapy‐naïve children with pLGG. Our results provide preliminary support, despite low sample size, for the use of everolimus as target therapy in pLGG showing lack of progression with a manageable toxicity profile. Abstract : What's new? Traditional therapeutic approaches for pediatric low‐grade glioma (pLGG) center on surgery and radiotherapy. Radiotherapy in particular, however, can have long‐term, detrimental impacts on patient health. Here, the authors investigated the use of everolimus as a post‐surgical, front‐line targeted therapy in a group of 10 chemo‐ and radiotherapy‐naïve children with pLGGs harboring alterations in mTOR signaling pathways. Front‐line everolimus therapy was associated with a high rate of clinical response, with disease stabilization in the majority of patients. Adverse effects were resolved following temporary everolimus interruption. These preliminary findings warrant further investigation of everolimus as a targeted therapeutic strategy for mTOR‐positive pLGG.